Rozwiąż równania
Zadanie 2

Odpowiedź:
2.
a)
2/3(x - 1) - 3 = (1 - x)/3 | * 3
2(x - 1) - 9 = 1 - x
2x - 2 - 9 = 1 - x
2x - 11 = 1 - x
2x + x = 1 + 11
3x = 12
x = 12/3 = 4
b)
x/2 - 1 = 3x - (x + 3)/2 | * 2
x - 2 = 6x - x - 3
x - 2 = 5x - 3
x - 5x = - 3 + 2
- 4x = - 1
4x = 1
x = 1/4
c)
(x - 3)/4 + 1 = 1/4 - 3x | * 4
x - 3 + 4 = 1 - 12x
x + 1 = 1 - 12x
x + 12x = 1 - 1
13x = 0
x = 0
d)
1/5 - 0,2x = 2/5x - 2(x + 3) | * 5
1 - 0,2x * 5 = 2x - 5 * 2(x + 3)
1 - x = 2x - 10(x + 3)
1 - x = 2x - 10x - 30
1 - x = - 8x - 30
- x + 8x = - 30 - 1
7x = - 31
x = - 31/7 = - 4 3/7